Substrate scope for trimethyllysine hydroxylase catalysis. Issue 87 (12th October 2016) - Al Temimi, Abbas H. K.; Pieters, Bas J. G. E.; Reddy, Y. Vijayendar; White, Paul B.; Mecinović, Jasmin
Abstract : Human trimethyllysine hydroxylase (TMLH) catalyses hydroxylation of substrates other than naturall -trimethyllysine. Abstract : Trimethyllysine hydroxylase (TMLH) is a non-haem Fe(ii ) and 2-oxoglutarate dependent oxygenase that catalyses the C-3 hydroxylation of an unactivated C–H bond inl -trimethyllysine in the first step of carnitine biosynthesis. The examination of trimethyllysine analogues as substrates for human TMLH reveals that the enzyme does hydroxylate substrates other than naturall -trimethyllysine.